Executive Professionalization and Executive Selection - Joseph A. Raelin (Human Resource Planning, 1997)
Executive management as a distinct occupational category from general management seems to be becoming increasingly professionalized. From a power perspective, CEOs dominate the decision-making apparatus of our major business enterprises. From an attribute approach to professionalization, there also appears to be an evolving executive skill set which could be applied across organizations and industries. Executive professionalization could contribute to the strategic leadership of our major organizations. This paper critically examines executive professionalization from both power and attribute perspectives. In particular, it considers whether the growing taste for outside successors in the CEO-selection decision results from professionalization. A database search finds that neither professionalized power considerations nor executive skills constitutes a critical basis for CEO external selection.
Keywords: D21; D23; D73; L22; M12; 330; Executive management; Professionalization; Selection; Upper echelon; Strategic leadership; Executive succession